Training Plan for the Continuity of Non-Presential Education in Six Peruvian Universities during COVID-19 - Pérez Sánchez, Lourdes (2022)
This article shows the response offered by the UTEC-UNED-TECSUP Consortium to six Peruvian public (national) universities aimed at strengthening the digital competences of their communities, made up of managers, teachers, students, and support technicians. The contextual and situational diagnosis, which covered organizational, technological, and competence dimensions, revealed a series of cross-cutting needs related to technological skills that prevented the training or mobilization of the digital competences necessary for progress in the other dimensions under study. The response was an online training plan, consisting of three training programs and eighty-three courses. The pedagogical strategy was based on the scaling of competence achievements that ended with problem-solving and applications in daily activities. The accompaniment was carried out through virtual tutorials, distributed via synchronous and asynchronous sessions. In total, 5034 were involved—347 were teachers and managers, 4932 were students, and 25 were technical staff. The pedagogical and socio-emotional limitations of the university community, as well as the scarcity of technological resources and poor connectivity, meant that the plan was only partially implemented. Moreover, the short and intense period of development to which the universities were subjected was also a factor.